Combustion and emission behaviors of dual-fuel premixed charge compression ignition engine powered with n-pentanol and blend of diesel/waste tire oil included nanoparticles. (15th September 2022) - Elumalai, P.V.; Kumar Dash, Santosh; Parthasarathy, M.; Dhineshbabu, N.R.; Balasubramanian, Dhinesh; Nam Cao, Dao; Hai Truong, Thanh; Tuan Le, Anh; Hoang, Anh Tuan
Graphical abstract: Highlights: Dual-fuel PCCI mode reduced NOx and smoke emissions significantly. Effects of n-pentanol addition on PCCI engine powered by tire oil were explored. n-pentanol prolonged the autoignition period and increased combustion duration. Adding CZ nanoparticles improved thermal efficiency and reduced HC/CO emissions. Abstract: The main aim of this study was to investigate the effect of n-pentanol percentage on the performance, combustion, and emission characteristics of a premixed charge compression ignition (PCCI) engine operated on dual-fuel mode. The primary fuel used in the engine was a blend of diesel fuel and pyrolytic oil, which was obtained from waste tires by the pyrolysis process. Moreover, CuO/ZnO (CZ) nanoparticles were added to the fuel blend to supply excessive oxygen for better combustion. In addition, n-pentanol is an ecologically innovative and cost-competitive compound used as a secondary fuel with high octane rating. For this experimental work, the fuel blend was prepared by adding 20% waste tire pyrolysis oil to 80% diesel fuel containing 50 ppm CZ nanoparticles, while n-pentanol was sprayed into the intake manifold with varying percentages, namely 10%, 20%, and 30%. As a result of the PCCI dual-fuel mode, PTO20CuZnO50P10 was found to be the best selection since it brought a significant decrement in emission parameters such as oxides of nitrogen (NOx), carbon monoxide (CO), hydrocarbon (HC), and smoke was 12%, 37%, 10%, and 23%, respectively, compared to the conventional diesel engine at peak load condition. However, it is recorded a reduction in brake thermal efficiency and an increase in specific fuel consumption under PCCI mode using PTO20CuZnO50P10 compared to the conventional diesel engine. In general, PTO20CuZnO50P10 was chosen as the best fuel for the PCCI mode of operation aiming to reduce pollutant emissions.